Molecular Chaperones as Targets to Circumvent the CFTR Defect in Cystic Fibrosis - Chanoux, Rebecca A.; Rubenstein, Ronald C. (Frontiers in Pharmacology, 2012)
Cystic Fibrosis (CF) is the most common autosomal recessive lethal disorder among Caucasian populations. CF results from mutations and resulting dysfunction of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR). CFTR is a cyclic AMP-dependent chloride channel that is localized to the apical membrane in epithelial cells where it plays a key role in salt and water homeostasis. An intricate network of molecular chaperone proteins regulates CFTR’s proper maturation and trafficking to the apical membrane. Understanding and manipulation of this network may lead to therapeutics for Cystic Fibrosis in cases where mutant CFTR has aberrant trafficking.